The Effect of Formulation Parameters on the Physical Properties and In-Vitro Dissolution Profile of Ethyl Cellulose-Theophylline Microspheres Using the Emulsion-Solvent Evaporation Process - Rammal, Hassan A (2020)
Controlled-Release drug delivery using microspheres depends on drug-encapsulation formulation, processing conditions, and excipient physical properties. Several parameters affect the microspheres’ formation and properties, including Physical, Chemical, and dissolution profile. This thesis aims to gain a better understanding of the number and type of parameters which affect the properties of Ethyl-Cellulose-Theophylline microspheres, and also attempts to explain the reason why said parameter affects said property in a certain specific way. In order to fully explore by which means drug-encapsulated microspheres are affected, this thesis looked at eight different parameters which were suspected to trigger changes in the properties of microspheres. The final aim of this thesis was to develop the most effective, efficient, and environmentally friendly method to form microspheres possessing the most beneficial properties for controlled release drug delivery